Filosofia E Teologia Na Perspectiva Da Escola Alexandrina = Philosophy and theology in the perspective of Alexandria's School - Sanches, Samuel (Vox scripturae, 2019)
This article presents reflections on philosophy and theology from the perspective of the Alexandria’s School, as well as its importance for our time. For this and in a first part we will deal with Alexandria, its history and also its philosophical tradition, with application to the literary philosophical schools in Alexandria and Neoplatonism. And secondly we will talk about Hellenistic Judaism, Christianity in late antiquity, the theory of religion between philosophy and practice, then about the myth and history of Christianity; finally, Jesus and the mythological discourse. Consequently, a philosophical discourse, especially from Alexandria, should be discussed, highlighting the doctrinal differences of theology in a synthesized way, thus promoting a redemption of bibliographical re-readings, thus contributing to a reflective basis of Alexandria’s remaining philosophical and historical elements.